Semantic Structure Of The Word (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the problem of the word in the science of linguistics, the structure of the word in languages of different systems and at different stages of language development, the semantic structure of the word. The question of some external - mainly phonetic or internal - grammatical or lexical-semantic features of the word is being resolved